EQUALITY OF OPPORTUNITY BETWEEN MEN AND WOMEN ON THE LABOUR MARKET – THE GENDER PAY GAP WITHIN THE EU MEMBER STATES - Stângaciu, Oana Ancuţa (Studies and Scientific Researches. Economics Edition, 2013)
The actions taken for the promotion of the equality of opportunity between men and women and for eliminating the direct or the indirect discrimination apply to the field of employment as well as to the field of education, health, culture, information and the participation in the decision making process. Starting from one of the objectives of the Strategy for the equality of opportunity, being aware of the real situation of women participation compared to men participation to the economical and social life, this analysis offers a perspective on the equality of opportunity between men and women in the field of employment, seen based on the statistical data. Thus, in order to quantify this phenomenon using methods specific to the statistical analysis, we used the gender pay gap indicator pertaining to the EU member states per total economy, as well as per economical activities, and the research results show that on the EU level there are still significant gender pay gaps.